INVERSE PROBLEM OF BIFURCATION THEORY FOR THIN-WALLED SYSTEMS THEORY - Obodan, N. I.; Adlutcky, V. J.; Gromov, V. O. (Computer Science and Applied Mathematics, 2016)
Paper focuses on an inverse bifurcation problem in thin-walled systems theory. The problem implies identification pre-bifurcation state of perturbed thin-walled system. The topological precursor used is based on typical sequences of deformed states extracted from clustered post-critical solutions of non-linear boundary problem of thin-walled systems theory. The proposed approach was employed to identify a pre-bifurcation state of a cylindrical shell under uniform pressure (close to the critical) subjected to a pulse impact.